Field robots development in the aspect of achieving the goals of sustainable agriculture. Issue 1 (1st March 2022) - Sobocki, S; Wojciechowski, J; Legutko, S; Mac, J; Zawada, M; Szymczyk, S
Abstract: The article deals with the issues related to the use of field robots in agricultural production in the aspect of the use of a sustainable farming system. At the beginning, the very essence of sustainable agriculture is presented and the problems that remain to be solved are identified, thus determining the market demand for autonomous field robots. The next part of the article presents the main division of agricultural robots and an overview of the most interesting solutions from the last few years that have been implemented by private companies and research centres from around the world. The review of available solutions makes it possible to identify the main challenges related to the implementation of robotic projects into working in difficult field conditions that are faced by the engineers who design them. The projects of autonomous robots used for work in agriculture, implemented by the Łukasiewicz Research Network - Industrial Institute of Agricultural Engineering in cooperation with consortium members, are also presented. At the end of the article, there is a summary and conclusions, which in a general sense define the need for further research on field robots, so as to achieve their fully autonomous work in the near future.